Analisis Isi Berita Corporate Social Responsibility (Studi kasus PT. BM) - Natalia Widiasari (Atma Jaya Indonesia Catholic University, Jakarta, 2012)
In the era of tight competition, business needs more than superior quality product and brand recognition to reserve a place in customer’s mind and heart. Businesses have been starting to implement CSR as the strategic business practice, which served as community relations as well as media relations. CSR is deﬁ ned as one of the differentiators in which factual feeds of CSR activities would attract media coverage. This article is a content analysis research based on secondary data using media coverage of BM’s CSR related activities to understand what makes them interesting.